PENGEMBANGAN MEDIA TIGA DIMENSI UNTUK MENINGKATKAN LIFE SKILLS MAHASISWA PENDIDIKAN SEJARAH IKIP PGRI MADIUN - Muhammad Hanif (Jurnal Pendidikan, 2008)
One out of some objectives  of carrying  out the scholarship  of the History Study  Program  of IKIP   PGRI Madiun  is to enhance:  (1) teachers  who have sufficient  competence   in their teaching  skill, (2) teachers  who are sensitive  towards  the progress  of the history and all social process within the society, 3) teachers  who are flexible  against the development   of history  of Indonesia    by  having  the historical awareness  as front-liners  of educational   conducts.  The competence copes  with competence   and qualification   at the cognitive,  affective and psychomotor  domains.  Such a competence   leads the learners  to life-skill    that   students  should   cope   with.  Among   some   ways developing  the lecturers competence  at the three domains  mentioned above  in generating   the, students   life-skill,   it  is  suggestible   that lecturers develop  teaching  method. Three-dimension   teaching  media is one  method  that  is presumptively   able  to develop  the lecturers' competence  in generating  the students'  life-skill. This research serves an analysis on the significance  of the use of three-dimension  teaching media  on  the  students’ life skill.  This  research,   then,  proposes objectives  as to identify the significance  of three-dimension   teaching media towards  the students'  life-skill.The research  method  applied  in this research  is Research  and Development  coping with three stages, i.e.: (1) exploration  under qualitative  descriptive  method, (2) development  under single one shot case study, (3) experimentation   method. The subjects of the study are all of the students of the History Study Program of IKIP PGRI Madiun.The research lasts in drawing conclusion  that the development of three-dimension   teaching  media can analytically  improve life skill of the students of History Study Program of IKIP PGRI Madiun. Then the hypothetic model as shown in figure 1 is attested already as it is shown in figure 2 and 3 under attested consistence and validity in generating the life-skill of the students of History Program of IKIP PGRI Madiun.